2003
DOI: 10.1007/s00296-003-0398-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum homocysteine level is higher in Behçet’s disease with vascular involvement

Abstract: This preliminary study suggests that elevated serum homocysteine levels may play some role in the development of venous and arterial thromboses in BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 15 publications
3
26
0
Order By: Relevance
“…However, the association between hcy and thrombosis remains statistically significant in many of the studies that considered in the analysis the impact of other potential risk factors, such as male sex or smoking habits. 8,12,25,[27][28][29][30]32,34,35 Furthermore, hcy appeared to be a risk factor for thrombosis even in the 2 studies in which immunosuppressive therapy had been withdrawn before measurement. 28,36 Third, 3 studies 4,25,28 have included also some patients with aneurysms as vascular manifestations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the association between hcy and thrombosis remains statistically significant in many of the studies that considered in the analysis the impact of other potential risk factors, such as male sex or smoking habits. 8,12,25,[27][28][29][30]32,34,35 Furthermore, hcy appeared to be a risk factor for thrombosis even in the 2 studies in which immunosuppressive therapy had been withdrawn before measurement. 28,36 Third, 3 studies 4,25,28 have included also some patients with aneurysms as vascular manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria were reported in 13 studies, 4 of them specified that patients taking drugs interfering with hcy levels were excluded. Thus, 4 studies were considered of high quality, 4,24,25,28 whereas the other 12 were considered of low quality. 8,12,26,27,29 -36 Hyperhomocysteinemia Eight studies, 4,12,26,27,30,32,35,36 for a total of 166 patients with thrombosis and 318 patients without thrombosis, were included in the metaanalysis.…”
Section: Study Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Elevated Hcy has also been reported to be associated with thrombosis in vascular BS in several studies. [18][19][20][21] Cerebral venous sinus thrombosis frequently co-occurs with peripheral venous vascular events such as deep venous thrombosis and pulmonary vascular disease; therefore, serum Hcy levels are expected to be high in vascular NBS. 22 Homocysteine is known to be toxic for endothelial cells and has also been found to be associated with lower cognitive scores and neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The increased E-selectin levels were associated with Behçet's disease particularly the eye, central nervous system involvement, and thrombosis activation [28]. Increases in homocysteine levels have been demonstrated in Behcet;'s disease patients in which thrombosis has developed, and it has been suggested that the level is more related to endothelin and nitric oxide [29,30]. Plasminogen activator inhibitor-1 levels were increased in thrombosis and arthritis atacks in Behçet's disease [31].…”
Section: Behcet's Diseasementioning
confidence: 99%